Non-destructive Testing of Wooden Elements in Historic Buildings - An Example of Testing a 19th Century Roof Truss Structure - Drobiec, Joanna; Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Destructive tests are not usually allowed in historic buildings; only non-destructive tests can be performed there. The obtained results should deliver the repair solutions that do not interfere into the historic layout of the church architecture and structure. One of the rarest areas subjected to non-destructive testing is diagnostic testing of wooden structures. However, calculations of strength verification cannot be performed if the wood class and quality are not determined.
Keywords: diagnostic testing of wooden structures; non-destructive tests; historic frame structures